2015
DOI: 10.1016/j.jhydrol.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of an urban community’s acceptance of a large desalination scheme for drinking water

Abstract: s u m m a r yChanging climates and growing populations have prompted policy makers to shift to more climate resilient, technology-driven water sources, such as seawater desalination. Desalination is a prominent water resource in the Middle East but countries in other parts of the world with similar scarcity issues and good access to sea water, such as Australia, have been comparatively slow to adopt it. This paper explores attitudes to desalination in Perth, Western Australia, and the factors that influence it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
(30 reference statements)
4
12
0
1
Order By: Relevance
“…Perceived negative impacts from the plant were the strongest predictors reducing support for seawater desalination in our study. This finding is similar to the results of Gibson et al (2015) who also found that perceptions about outcomes predicted support for proposed desalination plants. Perceived environmental impacts in our study included impacts on the marine ecosystem…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Perceived negative impacts from the plant were the strongest predictors reducing support for seawater desalination in our study. This finding is similar to the results of Gibson et al (2015) who also found that perceptions about outcomes predicted support for proposed desalination plants. Perceived environmental impacts in our study included impacts on the marine ecosystem…”
Section: Discussionsupporting
confidence: 89%
“…More than 70% of sampled residents supported the seawater desalination plant, which is similar to findings of Gibson et al (2015) who reported 73% and 74% support for future desalination plants in Perth, Australia, in 2007 and 2012. Perth, a large urban region, already receives about 39% of its water from two desalination plants (Water Corporation 2014).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Desalination is already a reality on much of the Mediterranean coast and it has even acquired the label of an ordinary supply source. Various authors have debated the role that may be played by desalination in water policy [14,20,21,[57][58][59]. As Baldwin and Uhlman [60] affirm, desalination may contribute to improving water security and it may become a secure source of long-term resources, with the flexibility that its production can decrease in the event of abundancy of other sources and increase in the case of drought episodes.…”
Section: Desalinated Water: a Strategic Resource During Drought Situamentioning
confidence: 99%
“…Such an assessment is critical to account for local preferences in the planning of desalination plants and to facilitate a more systematic approach to the planning of new facilities. While previous studies have investigated public attitudes towards desalination plants [24,30,41] and the acceptance of using desalinated water [19][20][21]65], an understanding of coastal stakeholders' management priorities for seawater desalination plants is lacking.…”
Section: Introductionmentioning
confidence: 99%